Gelastic Epilepsy and Hypothalamic Hamartoma - J Gordon Millichap (Pediatric Neurology Briefs, 1999)
The causes, clinical manifestations, and evolution of gelastic seizures (GS) were studied, using video-EEG and MRI, in 9 patients observed between 1986 and 1997 at the Epilepsy Center, Federico II University, Naples, Italy.